Analysis of the F2LR3 (PAR4) Single Nucleotide Polymorphism (rs773902) in an Indigenous Australian Population - Ningtyas, Dian; Thomson, Russell J.; Tarlac, Volga; Nagaraj, Shivashankar H.; Hoy, Wendy; Mathews, John D.; Foote, Simon J.; Gardiner, Elizabeth E.; Hamilton, Justin R.; McMorran, Brendan J. (Frontiers in Genetics, 2020)
The F2RL3 gene encoding protease activated receptor (PAR) 4 contains a single nucleotide variant, rs773902, that is functional. The resulting PAR4 variants, Thr120 and Ala120, are known to differently affect platelet reactivity to thrombin. Significant population differences in the frequency of the allele indicates it may be an important determinant in the ethnic differences that exist in thrombosis and hemostasis, and in patient outcomes to PAR antagonist anti-platelet therapies. Here we determined the frequency of rs773902 in an Indigenous Australian group comprising 467 individuals from the Tiwi Islands. These people experience high rates of renal disease that may be related to platelet and PAR4 function and are potential recipients of PAR-antagonist treatments. The rs773902 minor allele frequency (Thr120) in the Tiwi Islanders was 0.32, which is similar to European and Asian groups and substantially lower than Melanesians and some African groups. Logistic regression and allele distortion testing revealed no significant associations between the variant and several markers of renal function, as well as blood glucose and blood pressure. These findings suggest that rs773902 is not an important determinant for renal disease in this Indigenous Australian group. However, the relationships between rs773902 genotype and platelet and drug responsiveness in the Tiwi, and the allele frequency in other Indigenous Australian groups should be evaluated.